A MULTICRITERIA DESCRIPTION OF RULES FOR PUBLIC PROCUREMENT - MALIŠA ŽIŽOVIĆ; MILUTIN ŽIVKOVIĆ (Journal of Engineering Studies and Research)
At an announced tender of a contracting party, in the processes of public procurement of goods or services, a method of decision-making follows after interested bidders submit bids. Such method of choice is characteristic for all business systems with majority share of state capital. Methods of decision-making come down to selecting the best bids, because mistakes in the selection should be excluded. However, in practice, the problems of a wrong choice are manifested in dissatisfaction of the bidders. The problem then causes a delay in the procurement process, and often the retrial. In order to prevent this from happening authors of this paper suggest a somewhat different methodologies in selecting the most advantageous tender to the contracting authorities. The proposed method will be the case of the of Parking service (PC) from Belgrade (service of overhaul of the devices) will show a possible way of selecting the best alternative bids, taking into account previously adopted criteria.